Z historii PRL : dziennikarze - Waglewski, Jerzy (Warszawa : Wydawn. Iskry, 2003)
A collection of works by Polish journalists who add to the history of Poland during the communist regime.
Keywords: Journalists -- Poland -- Biography; Poland -- History -- 1945-